THE PREVALENCE AND CLINICAL FEATURES OF GOUT AND CALCIUM PYROPHOSPHATE DEPOSITION DISEASE IN PATIENTS WITH ACUTE ARTHRITIS - M. S. Eliseev; S. A. Vladimirov (Научно-практическая ревматология)
Objective: to study the rate of gout and calcium pyrophosphate deposition disease (CPDD) and to provide their clinical characteristics in patients with acute arthritis.Subjects and methods. The investigation enrolled 150 patients (97 men and 53 women) with acute mono- or oligoarthritis of no more than 2 weeks’ duration who had visited the Outpatient Department of V.A. Nasonova Research Institute of Rheumatology. Their mean age was 60.2±12.0 years (range, 28–76 years). All the patients underwent inflamed joint puncture and synovial fluid (SF) crystal identification by polarized microscopy using an Olympus CX31-P compensator.The diagnosis of CPDD was established in compliance with the criteria elaborated by D. McCarty. Gout was diagnosed only when sodium monourate (SMU) crystals were found in SF.Results and discussion. The investigation revealed gout in 51 (34%) patients, CPDD in 45 (30%), coincidence of gout and CPDD in 15 (14%), and 39 (26%) patients had other diseases: 15 (10%) – osteoarthritis, 6 (4%) – rheumatoid arthritis, 5 (3%) – septic arthritis, 5 (3%) – psoriatic arthritis, 2 (1%) – ankylosing spondyloarthritis, 4 (3%) – injury, and 5 (3%) – undifferentiated spondyloarthritis. There were 40 men and 11 women among the patients with gout and 13 men and 32 women among those with CPDD. The patients with gout were younger than those with CPDD (35.5±8.9 and 58.4±12.8 years, respectively; p < 0.05). In the patients with CPDD, knee, ankle, and first metatarsophalangeal joint arthritis was present in 34 (76.3%), 17 (30.3%), and 4 (9%) cases, respectively. Arthritis developed within a few hours in 90% of the patients with gout and in 33.3% of those with CPDD (p < 0.001). Monoarthritis was significantly more common in gout whereas oligoarthritis – in CPDD (p < 0.05). Visual analog scale pain intensity averaged 78.4±12.5 mm and 54.32±22.02 mm (p < 0.05), duration of arthritis – 10.3±3.8 days and 3.4±2.1 days (p < 0.05) in gout and CPDD respectively.Conclusion. CPDD is the most common (60%) cause of acute arthritis in women and the second most frequent (13%) cause in men (following gout). Acute arthritis develops more slowly and persists for a longer period of time in patients with CPDD than in those with gout.